2006
DOI: 10.1124/mol.106.024547
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin Inhibits Immunostimulatory Function of Dendritic Cells: Implication of Immunotherapeutic Adjuvant

Abstract: Apigenin, one of the most common flavonoids, has been shown to possess anti-inflammatory, anticarcinogenic, and free radical-scavenging properties. However, the influence of apigenin on the immunostimulatory effects and maturation of dendritic cells (DC) remains, for the most part, unknown. In this study, we have attempted to ascertain whether apigenin influences the expression of surface molecules, dextran uptake, cytokine production, and T-cell differentiation as well as the signaling pathways underlying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 37 publications
3
46
0
1
Order By: Relevance
“…Other studies demonstrate the ability of lavonoids as NF-κB inhibitors and their role in preventing NF-κB signaling pathway-mediated disorders. It is identiied that apigen, quercetin, kaempferol, rutin is a potent inhibitor of NF-κB, which may perform a pivotal function in the regulation of cell growth, apoptosis and the regulation of the cell cycle [57][58][59]. Overall, the results indicated that lavonoids suppress the activation of NF-κB and NF-κB-regulated gene expression, leading to enhancement of apoptosis.…”
Section: Antiproliferative Efectmentioning
confidence: 60%
“…Other studies demonstrate the ability of lavonoids as NF-κB inhibitors and their role in preventing NF-κB signaling pathway-mediated disorders. It is identiied that apigen, quercetin, kaempferol, rutin is a potent inhibitor of NF-κB, which may perform a pivotal function in the regulation of cell growth, apoptosis and the regulation of the cell cycle [57][58][59]. Overall, the results indicated that lavonoids suppress the activation of NF-κB and NF-κB-regulated gene expression, leading to enhancement of apoptosis.…”
Section: Antiproliferative Efectmentioning
confidence: 60%
“…It has been well characterized that in chronic asthma, Th2 lymphocytes infiltrate the lungs and produce inflammatory cytokines, including IL-4, IL-5, and IL-13 (21). These cytokines may induce the expression of inflammatory molecules in both the endothelial cells of the bronchial circulation and the epithelial cells in the airway, and they may also promote the recruitment of lymphocytes and eosinophils (22).…”
Section: Discussionmentioning
confidence: 99%
“…The cell suspension was then washed twice with PBS for 5,6-carboxyfluorescein diacetate succinimidyl ester (CFSE) labeling. CFSE labeling of responder cells was undertaken as previously described (6,37). The cells were resuspended in 1 mM CFSE (Molecular Probes, Eugene, OR, USA) in PBS and periodically shaken at room temperature for 10 min.…”
Section: Irisflorentin Modifies Properties Of Dendritic Cellsmentioning
confidence: 99%